THE EFFECTIVENESS OF A PROPOSED PROGRAM BASED ON INTEGRATED EDUCATIONAL MODULES TO DEVELOP SEX EDUCATION FOR KINDERGARTEN CHILDREN - Abdulahmeed, Mohammed Ibrahim (European Scientific Journal, ESJ, 2013)
The current study aims at helping children to acquire some sex- related concepts through a program based on the integrated educational modules. The importance of the research lies in introducing a standardized program to develop some kindergarten children's sex concepts and help them expand their understanding concerning certain sex concepts. The study is also an effort to make up for the lack of similar studies in the field on one of the sensitive topics that many researchers avoid writing about. The research also aims at highlighting the ways of handling kindergarten children when discussing the concept of sex practically and educationally.